MASCULINITY, POWER, AND IDENTITY CONSTRUCTION IN THE GREAT GATSBY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article offers an extended analysis of masculinity, power, and identity construction in The Great Gatsby by F. Scott Fitzgerald. Situating the novel within the socio-cultural framework of 1920s America, the study examines how competing models of masculinity—hegemonic, aspirational, and reflective—are constructed through class hierarchy, economic capital, and symbolic performance. Drawing on gender theory, particularly R. W. Connell’s concept of hegemonic masculinity, this paper argues that Fitzgerald exposes masculinity as a performative and unstable construct deeply intertwined with wealth and social recognition. Through close reading of Tom Buchanan, Jay Gatsby, and Nick Carraway, the article demonstrates that masculine identity in the novel is shaped not only by personal ambition but also by structural inequalities embedded in the American Dream. Ultimately, Fitzgerald critiques the illusion of stable masculine power, revealing its dependence on social validation and inherited privilege.